PENGEMBANGAN KEMAMPUAN MENULIS ANAK USIA DINI DENGAN TEMA ALAM SEMESTA - Rita Kurnia (Jurnal Educhild : Pendidikan dan Sosial, 2018)
The writing of this paper aims to describe the development of early childhood writing skills withthe theme of the universe. Writing is a person’s ability to write letters and numbers that can becoupled into words or sentences that have meaning or meaning. Writing skills such as writingletters or symbols, words, and numbers using pencils, pens, crayons or other stationery. Theauthor can use the observation method to get the ability to develop early childhood writing with thetheme of the universe. The method used in the experiment, conversing to adjust the story in aromantic performance, an event to be impressive or touching, or drama or poetry reading. Withthe theme of the universe, sub-themes of natural disasters in children’s picture books candevelop children’s writing skills, there are types of communication tools that make children loveto chat, express, and children can also write letters, sounds, symbols, vocabulary , poetry, poetry,and poetry in accordance with the theme, can also stimulate the growth of the child’s brain. Indeveloping tourism media (visiting evacuation sites for natural disasters) and puzzle games, theimplementation of the Media World can develop cognitive, motoric, language, social emotional,moral, artistic and literary aspects of children through poetry, poetry, poetry applied to each learningtheme.  anak usia dini dengan tema alam semesta. Menulis adalah kemampuan seseorang dalammenulis huruf dan angka yang dapat dirangkaikan menjadi kata atau kalimat yang memilikimakna atau arti. Kemampuan menulis seperti menulis huruf atau simbol, kata, dan angkamenggunakan pensil, pena, crayon atau alat-alat tulis lainnya. Penulis dapat menggunakanmetode observasi untuk mendapatkan mengembangkan kemampuan menulis anak usia dinidengan tema alam semesta. Metode yang digunakan eksperimen, bercakap-cakap untukpenyesuaian cerita dalam pertunjukan pendramaan, suatu peristiwa menjadi mengesankanatau mengharukan, atau pembacaan puisi atau prosa secara drama. Dengan tema alamsemesta, sub tema bencana alam dalam buku cerita bergambar anak dapat mengembangkankemampuan menulis anak, ada jenis-jenis alat komunikasi sehingga membuat anak senanguntuk bercakap-cakap, berekspresi, dan anak juga dapat menuliskan huruf, bunyi, simbol, kosakata, puisi, pantun, dan syair sesuai dengan tema, juga dapat merangsang pertumbuhan otakanak. Dalam pengembangan media karya wisata (berkunjung tempat pengungsian bencanaalam) dan permainan puzzle Implementasi Media alam semesta ini dapat mengembangkanaspek kognitif, motorik, bahasa, sosial emosional, moral, seni dan sastra anak melalui puisi,pantun, syair diterapkan disetiap tema pembelajaran.